Effects of Sintering Temperature on Physical Properties, Phase, Microstructure and Oxygen Stoichiometry of Nay CoO2 Ceramics - Pimpilai Wannasut (Science Faculty of Chiang Mai University, 2019)
Due to the stability in air, low cost and non-toxicity, oxide thermoelectrics have been considered a potential candidate for high-temperature waste-heat recovery devices. In this study, the effects of sintering temperature on phase, microstructure and oxygen content of NayCoO2 (NCO) ceramics were investigated. The NCO ceramics were prepared by conventional solid-state reaction and sintering methods. The sintering condition included a temperature range of 800-950 ฐC and 18 h sintering time. The ceramic with a highest density value of 4.76 g/cm3 was obtained by being sintered at 900 ฐC with the linear shrinkage of ~12%. X-ray diffractometry and Raman spectroscopy were used for phase analysis. The microstructure was determined by scanning electron microscopy. The change in oxygen stoichiometry was discussed in relation with the crystal structure and microstructural characteristics in order to elucidate the stability of this compound for high-temperature operation of thermoelectric device.